The uses and misuses of politics : Karl Rove and the Bush presidency - Mayer, William G., 1956- (University Press of Kansas, 2021)
"In 2001, a newly-elected Republican president went to Washington, hoping not just to serve out eight years in the White House but to change the governing philosophy of his party and to launch a new era of Republican electoral majorities. He failed. This book is the first detailed analysis of the interaction between politics and policy in the Bush 43 presidency: about what he hoped to accomplish politically and how and why he failed. The central characters in this story are Bush himself and Karl Rove, Bush's chief political advisor, perhaps the most powerful political consultant in American history. Rove's ambition was to create the next realignment: to usher in an extended era of Republican electoral dominance. By late 2008, as the Bush presidency entered its final months, there was talk of realignment, but now it was the Democratic Party that controlled the presidency and both houses of Congress and was widely thought to be putting together a new majority coalition. This book explains what went wrong and how the political missteps and policy failures of Bush's advisor hold important lessons for future American presidents"-- Provided by publisher
Keywords: Rove, Karl.; Rove, Karl -- Influence.; Bush, George W. -- (George Walker), -- 1946-; Republican Party (U.S. : 1854- ) -- History -- 21st century.; Rove, Karl; Republican Party (U.S. : 1854- ); United States -- Politics and government -- 2001-2009.; Political consultants -- United States.; États-Unis -- Politique et gouvernement -- 2001-2009.; Conseillers politiques -- États-Unis.; Political Parties.; Political Process.; POLITICAL SCIENCE.; Conservatism & Liberalism.; Political Ideologies.; American Government.; United States; Politics and government; Political consultants; Influence (Literary, artistic, etc.); 2000-2099; Electronic books.; History